PENGEMBANGAN E-LKM BERBASIS GUIDED INQUIRY LEARNING BERBANTUAN DISCORD UNTUK MENINGKATKAN MOTIVASI BELAJAR MURID PADA MATERI IKATAN KIMIA FASE F : UJI VALIDITAS - Isabellinda; Rahadian Zainul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the use of conventional Student Worksheets (LKM) that have not optimally facilitated students in conducting inquiry, constructing concepts, and actively engaging in learning chemistry, particularly in the abstract topic of chemical bonding. This study aimed to develop an Electronic Student Worksheet (E-LKM) based on Guided Inquiry Learning assisted by Discord for Phase F chemical bonding and to determine the validity and initial student responses to the developed product. This study employed an Educational Design Research approach using the Plomp development model, which was limited to the development or prototyping phase, particularly the one-to-one evaluation. Product evaluation consisted of self-evaluation, expert review, and one-to-one evaluation. Product validity was analyzed using Aiken’s V index, while student responses were analyzed using a five-point Likert scale. The results of the expert review showed that the E-LKM obtained an average Aiken’s V value of 0.87, categorized as valid. The one-to-one evaluation involving three students showed a “Strongly Agree” category across all assessed aspects, including clarity (4.53), attractiveness (4.60), engagement (4.58), learning motivation (4.53), and errors and improvements (4.56). Thus, the E-LKM based on Guided Inquiry Learning assisted by Discord was considered valid and received positive responses from students, indicating its potential as an interactive digital learning material to support student engagement and learning motivation in Phase F chemical bonding.